M2 acoustic presence of marine mammals and anthropogenic noise manually counted for the period 2019-2020 - Llobet, Samuel M.; Ahonen, Heidi; Kovacs, Kit M.; Lydersen, Christian (Norwegian Polar Institute, 2023)
M2 acoustic presence of marine mammals and anthropogenic noise manually counted for the period 2019-2020